The Psychological Factors on the Final Year English Literature Students Study Program Of Universitas Dehasen Bengkulu Through Whatsapp Chats - Erbakan, Muhammad Ichsan; Putra, Dhanu Ario; Rullyanti, Merry (Amirul Bangun Bangsa Publishing, 2026)
This research, entitled “The Psychological Factors On The Final Year English Literature Students Study Program Of Universitas Dehasen Bengkulu Through Whatsapp Chats”, aims to identify the psychological factors influencing students in completing their thesis, focusing on motivation, self-esteem, and anxiety. Using a descriptive qualitative method with questionnaires and interviews, the findings show that WhatsApp plays a dual role in students’ academic experience. In terms of motivation, nine out of ten respondents stated that WhatsApp increased their enthusiasm through quick communication, knowledge exchange, and emotional support. Regarding self-esteem, six students felt more confident expressing academic opinions via WhatsApp, while four preferred face-to-face communication. However, nine respondents also admitted experiencing anxiety, particularly when waiting for feedback or receiving urgent messages from supervisors. Overall, this study concludes that WhatsApp can simultaneously enhance motivation and confidence while also triggering anxiety, supporting Brown’s (2007) theory that psychological factors significantly affect academic performance